'Sacrifical lambs' or candidate mimicking? Gender-based nomination strategies in elections. (July 2022) - Martínez i Coma, Ferran; Lago, Ignacio
This paper explores an alternative mechanism for understanding the drivers of the nomination of women for elective office in single-member electoral systems. Previous research has generally examined two sources of gender-based politics: party ideology, with leftist parties being more female-friendly than rightist parties, and the strategic nomination of candidates depending on whether the party is expected to win or lose in the district, with women more likely to be used as 'sacrificial lambs' in hopeless contests. We argue that the nomination of male and female candidates across districts reflects an interdependence of party strategies – in particular, the actions of the main opposition party. We hypothesise that when the trailing party is not committed to gender equality, its equilibrium strategy in a given district is the nomination of a candidate of the same gender as that of the front-running party. Secondary data from 1, 017 single-member Australian districts and more than 2, 000 candidates from 2001–2019 confirm our hypothesis.